Nilai Ekonomi Air Daerah Aliran Sungai (DAS) Way Orok Sub Das Way Ratai Desa Pesawaran Indah Kecamatan Padang Cermin Kabupaten Pesawaran - Pices Raini Dwi Putri; Slamet Budi Yuwono; Rommy Qurniati (Department of Forestry, Faculty of Agriculture, University of Lampung, 2013)
This study aims to know the public perception of water usage and to determine the economic value of water from any use of and willingness to pay for forest and land rehabilitation.This research is held on March-Mei 2012 at Pesawaran Indah village, Padang Cermin, Pesawaran.To predicted the total economic value of water resources were used WTP method. The results of this study showed the total economic value of water is as much as Rp 1.705.844.764,-/year.These show that the public has higher willingness to pay of the total value, so it can be concluded that assess a community resource, Pesawaran Indah village has a perception of the water use is still low. One of factor is the exceeding availability of water resources, the community habit as free rider. It needs a policy of water management to maintain and conserve the water resources. Keywords: economic values of hydrologic, WTP (willingness to pay)